A Quantitative Assessment of Apoptotic Index with Varying Histological Degree of Dysplasia and Squamous Cell Carcinoma of Oral Cavity - A Light Microscopic Study - Chitrapriya Saxena; Vijay Wadhwan; Vijay Kumar; Aparna Singh; Siddharth Anand; Asib Ahmad (Indian Journal of Dental Research)
Aim and Objective The aim of the present study was to quantitatively assess the apoptotic index at a light microscopic level in hyperkeratosis with varying histological degrees of dysplasia and different grades of oral squamous cell carcinoma (OSCC) and its correlation with prognostic significance. Study Design The study included the histo-pathologically diagnosed cases of hyperkeratosis with varying degrees of dysplasia and different grades of OSCC, which were retrieved from the archives of the department, and clinical details were retrieved from the case records of the patients. The sample size consisted of 80 biopsied cases, divided into seven groups of 10 experimental cases and one group of 10 cases of normal mucosa as a control group. Results The age range of 50-59 shows maximum patients of hyperkeratosis with varying degrees of dysplasia and OSCC. Maximum apoptotic bodies were seen in cases of severe dysplasia and well-differentiated cases of OSCC. There was an observational difference noticed in apoptotic bodies between the patients who had less than 1-year disease-free survival rate. Conclusions The apoptotic cells are being seen using routine light microscopy techniques with hematoxylin and eosin staining. In different grades of squamous cell carcinoma, a decrease in the apoptotic count was noticed from well-differentiated squamous cell carcinoma toward poorly differentiated squamous cell carcinoma cases. Increased mean apoptotic bodies were observed in patients showing less than 1 year of survival.